Surface Runoff Modelling of Alanthurai Watershed Using Artificial Neural Networks - C. Meiaraj,; R.Sundararajan, (Journal of Soil and Water Conservation, 2022)
Water is fast becoming a scarce commodity in most part of the world. A study was carried out to estimate the surface runoff potential of the Alanthurai watershed located in the western part of the Coimbatore district in Tamil Nadu state using artificial neural networks (ANN).In this project, a simulation model has been created which can predict the runoff. The recurrence interval concept was used to calculate the rainfall for the future period. In general, ANN models, applied to the rainfall-runoff transformation problem, show encouraging results ANNs enable comparable or even better performance than a conceptual model.